Razširjenost finančnih ugodnosti za invalide v Sloveniji - Bitenc, Črtomir (Socialno delo, 2015)
The number of people with disabilities or people who have to deal with this or that handicap worldwide has been gradually increasing. However, the data show that people with disabilities have on average a much lower socio-economic status than others as a result of a more challenging entry into the labour market and thus more frequent unemployment. The report shows the extent to which providers of various services in Slovenia via various financial benefits relieve financial hardship of people with disabilities. Data collection took place during 2014 and mainly by help of municipalities and certain other institutions and organizations. Fields of benefits are divided into four categories: transport, culture, tourism, and sports & leisure.
Keywords: invalidnost; finančne ugodnosti; promet; culture; kultura; tourism; turizem; proti čas; Slovenia; Slovenija